La regulación del Cannabis Medicinal en el Perú - Loayza Ormachea, Carlos (2023)
The article develops the current regulatory framework for Medical Cannabis in Peru. At first, it presents and develops certain key concepts to understand the medicinal properties of Cannabis and its components. Subsequently, it analyzes the relationship between the fundamental right to health and its elements with Medical Cannabis. Then, it analyzes both its legal and regulatory framework and, finally, it analyzes its deficiencies and offers proposals to improve it from a regulatory perspective.